Development of Audiovisual Learning Media: Dyeing Spun Silk Yarn Using Ketapang Leaf Extract - Dimas Hartandi; Sukemi Sukemi; Farah Erika (FKIP - Universitas Riau, 2026)
This study aimed to develop and validate an instructional video on dyeing spun silk using ketapang leaf extract as an ethnochemistry-based contextual learning medium. The study employed a Design and Development (D&D) approach using the Planning–Production–Evaluation (PPE) model. Validation was conducted by two subject content experts and two media experts. The results showed that the developed video achieved a very high validity level, with an average validity score of 100% for both subject content and media aspects. The reliability analysis also indicated a perfect agreement score (100%). These findings suggest that the instructional video met the criteria for suitability in terms of content accuracy, media design, and technical quality. In addition, the visualization of the dyeing process helped explain abstract chemical concepts, such as the interaction between natural dyes and fibers as well as color transformation processes, thereby supporting students’ conceptual understanding. Nevertheless, this study was limited to the expert validation stage and did not examine the effectiveness of the media on students’ learning outcomes in broader educational settings. Practically, the video can serve as a digital demonstration tool and contextual learning resource for sustainability-oriented textile chemistry instruction.